Blisters on their feet : tales of internally displaced persons in India's North East - Das, Samir Kumar, 1961- (New Delhi : SAGE Publications, 2008)
Proceedings of four workshops organized by the Indian Council of Social Science Research-North Eastern Regional Centre.
Socio-economic portents of displacement of indigenous peoples / P. K. Mondal & M. C. Behera -- Proposed Subansiri Hydel project : a case study of potential displacement / Timo Riba -- Displacement and refugee issue in Arunachal Pradesh / P. K. Panigrahi -- A case study of the Sulungs (Puroiks) / Sristidhar Dutta & Tana Showren -- Internally displaced persons of Changlang district / K.O. Sebastian -- Environment-induced IDPs : an appraisal / Nazmin Banu Islam -- Riverbank erosion affected people in the Kamrup district / Aparna Goswami & Baneswar Das -- Erosion-induced displacement in Nagaon, Morigaon, Barpeta, Dhubri and Goalpara districts / Jyotirmay Jana -- Conflict and displacement : a case study of the election violence in 1983 / Makiko Kimura -- The displaced Santhals of Western Assam / Biswajit Chakrabarty -- IDPs of Western Assam : a study of conflict-induced displacement / Subhas Barman -- Nobody's people : Muslim IDPs of Western Assam / Uddipana Goswami -- The displaced Reangs of Hailakandi district / Abdul Mannan Mazumder & Bornali Bhattacharjee -- Kuki-Naga conflict and its impact on the Zeliangrong people / K. Gailangam -- A study of ethnic conflicts in the Hills, 1992-93 / Ksh. Bimola Devi -- IDPs of Manipur Hills / Koijam Shethajit -- A case study of the May 1993 riot victims of Purum Pangaltabi / S. Mangi Singh -- A note on the internally displaced persons / R. K. Ranjan Singh -- IDPs and the problems of their education / L. Leiren Singh -- Internally displaced persons in Tripura : past and present / Mahadev Chakravarti -- Development and development : a case study of the IDPs / Satyadeo Poddar -- Gumti Hydel project and the displaced persons / Malaya Banerjee -- Landownership and occupational patterns of IDPs (1999-2001) : a case study / Ruma Sahu & Amitabha Sinha -- Internal displacement : a man-made tragedy / Sukhendu Debbarma -- The case of Urabari Mohanpur block / Chandrika Basu Majumdar -- Birth of a problem / Sudhir Kumar Singh & Sristidhar Dutta -- Paradigm of development : a critique / Deepak Mishra -- Waiting for elusive resettlement and rehabilitation? / Monirul Hussain -- Challenges ahead / Subir Bhaumik -- Development, displacement and the right to life / Walter Fernandes & Sanjay Barbora.
Includes bibliographical references and index.
Keywords: Internally displaced persons -- India, Northeastern -- Social conditions; Internally displaced persons -- Government policy -- India, Northeastern; Social conflict -- India, Northeastern; Economic development -- India, Northeastern